The Influence of Organizational Variables Toward Performance of the Lecturers - Purwoatmodjo, Djumadi (Universitas Brawijaya, Indonesia, 2008)
Objectives of the research are, first, to analyze the influence of resources, leadership, reward, job design and structure variables toward performance of the lecturers. Second, it is conducted to analyze the most dominant variable toward performance of the lecturers. The research used data analysis technique of multi-linear regression analysis along with simultaneously and partially testing. Result of the analysis shows that the variable which has significant influence toward performance of the lecturers and variable that having the most dominant influence toward performance is reward variable.